Opera as Trans-Atlantic Culture in Pre-Confederation British North America: Mozart’s “Crudel! perchè finora” on an 1844 Toronto Concert Programme - Guiguet, Kristina (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2007)
AbstractWhy was Mozart’s duet, “Crudel! perchè finora” (Le Nozze di Figaro, III (i)) among the operatic excerpts sung by amateur and professional musicians at Mrs. Widder’s private Toronto soirée musicale? Typically Victorian, the formal programme for this musical party mixed opera with glees, popular ballads, and instrumental music, but the Mozart duet is rarely found on such programmes. The British hostess may have relied on her socially prominent audience in colonial Canada to recognize that her concert echoed the programming practices of London (England), as she positioned the concert to support her husband’s politically-sensitive land development plans. This example of trans-Atlantic culture suggests that Victorian amateur concert programmes are useful sources for audience reception history.